2021
DOI: 10.1017/s002428292000033x
|View full text |Cite
|
Sign up to set email alerts
|

Crittendenia gen. nov., a new lichenicolous lineage in the Agaricostilbomycetes (Pucciniomycotina), and a review of the biology, phylogeny and classification of lichenicolous heterobasidiomycetes

Abstract: The lichenicolous ‘heterobasidiomycetes’ belong in the Tremellomycetes (Agaricomycotina) and in the Pucciniomycotina. In this paper, we provide an introduction and review of these lichenicolous taxa, focusing on recent studies and novelties of their classification, phylogeny and evolution. Lichen-inhabiting fungi in the Pucciniomycotina are represented by only a small number of species included in the genera Chionosphaera, Cyphobasidium and Lichenozyma. The phylogenetic position of the lichenicolous representa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…Many Tremellomycetes have a dimorphic life cycle (Bandoni, 1995), but lichen‐associated Tremella species have been mainly studied when they form sexual fruiting bodies (basidiomata) on the lichen thalli or on/in the fruiting bodies (apothecia) of the ascomycete lichen symbiont. Thus, for most species only the filamentous life stage is well known and has been studied in detail (Diederich, 1996; Millanes et al ., 2021). However, in a recent study Tuovinen and colleagues (2019) showed that Tremella lethariae has a common and widespread yeast stage in thalli of Letharia and seems to enter the sexual cycle only rarely.…”
Section: Introductionmentioning
confidence: 99%
“…Many Tremellomycetes have a dimorphic life cycle (Bandoni, 1995), but lichen‐associated Tremella species have been mainly studied when they form sexual fruiting bodies (basidiomata) on the lichen thalli or on/in the fruiting bodies (apothecia) of the ascomycete lichen symbiont. Thus, for most species only the filamentous life stage is well known and has been studied in detail (Diederich, 1996; Millanes et al ., 2021). However, in a recent study Tuovinen and colleagues (2019) showed that Tremella lethariae has a common and widespread yeast stage in thalli of Letharia and seems to enter the sexual cycle only rarely.…”
Section: Introductionmentioning
confidence: 99%
“…3). It is likely that the same trend will continue and the diverisity of dimorphic yeast-like taxa will be increase in the following ten years with more new species and genera described in the future (e.g., Millanes et al 2021). Exploration of as yet understudied regions and environments, as well as a more precise identification of cryptic morphologically indistinguishable species will substantially contribute to the species diversity in these fungi.…”
Section: Discussionmentioning
confidence: 99%
“…The taxon sampling for each analysis was constructed based on the blast similarity sequence results and on the groups and sequences retrieved from previous phylogenetic studies; sequences of type materials were included when available (Supplementary Tables S1eS6). The taxon sampling of Agaricostilbomycetes was based on Millanes et al (2021) and Diederich et al (2022), that of Cystobasidiomycetes on Cernajov a and Skaloud (2019) and Millanes et al (2016a,b), that of Microbotryomycetes on Kachalkin et al (2019) and Yurkov et al (2016), and that of Ustilaginomycetes on Li et al (2017) and Wang et al (2015a). For the class Tremellomycetes, two separate MSAs were prepared, one for the order Tremellales and the other for Filobasidiales.…”
Section: Sampling Ementioning
confidence: 99%
“…Dimorphism, i.e., the alternating formation of both a haploid unicellular yeast phase and a dikaryotic filamentous mycelium during their life cycle, is common in basidiomycetes (Bandoni, 1995;Boekhout et al, 2011;Oberwinkler, 1987;Sampaio, 2004;Millanes et al, 2021). In his revision about Pucciniomycotina yeasts, Oberwinkler (2017) suggested that, as is the case for other basidiomycete yeasts, the Cyphobasidiales yeasts in lichens are a part of the lifecycle of these basidiomycetes growing and forming large colonies inside the lichen thalli.…”
Section: Introductionmentioning
confidence: 99%